How we can protect the protectors: learning from police officers and staff involved in child sexual abuse and exploitation investigations - Redmond, Theresa; Conway, Paul; Bailey, Simon; Lee, Peter; Lundrigan, Samantha (Frontiers in Psychology, 2023)
Abstract Background. Police officers and staff who work in child sexual abuse and exploitation (CSAE) investigations are routinely exposed to traumatic materials and situations. Despite support services, working in this space can have negative impacts on wellbeing. This paper explores the experiences and perceptions held by police officers and staff involved in CSAE investigations in the UK, regarding work-related wellbeing support and barriers to accessing such support. Method. A sample of 661 serving police officers and staff working in CSAE investigations participated in a UK-wide ‘Protecting the Protectors’ survey. We analysed quantitative and qualitative responses relating to participants’ experiences and perceptions regarding three main areas: 1) availability, usage and helpfulness of existing work-based well-being support; 2) barriers to accessing support, and: 3) desired support services. Findings. Five interconnected themes emerged from the qualitative data that represented participants’ experiences and views of work-based wellbeing support and the barriers to accessing it. These were ‘Lack of trust’, ‘Stigma’, ‘Organisational approaches to wellbeing’, ‘Barriers to support services’, and ‘Internalised barriers’. The findings suggest that while respondents were aware of work-based support, they indicated most frequently that they ‘never or almost never’ used them. Respondents also identified barriers to accessing support, which related to a perception of a critical or judgmental workplace culture and indicating a lack of trust in their organisations. Conclusions. Stigma regarding mental ill health has a pervasive and harmful impact on emotional health and wellbeing of police officers and staff involved in CSAE investigations, which creates a sense of lack of emotional safety. Therefore, eliminating stigma and creating a workplace culture that explicitly values and prioritises the emotional health and wellbeing of the workforce would improve the wellbeing of officers and staff. Police organisations could further improve CSAE teams’ wellbeing by developing a continuum of care which is available to workers from recruitment to the end of the role, training managers and supervisors to better support CSAE teams, improving workplace practices, and ensuring high quality, specialist support services are readily and consistently available across forces.